Profil Metabolit Volatil dan Non Volatil Bangle Hitam - Wardayanie, Ning Ima Arie; Prangdimurti, Endang; Hunaefi, Dase; Batubara, Irmanida; Tunnisa , Fitra; Rosalina, Dian; Afriyanti , Ani; Yuliana , Nancy Dewi (Jurnal Teknologi dan Industri Pangan, 2025)
The study discovering chemical compounds of black bangle (Zingiber ottensii Val.), which is a member of Zingiberaceae family, is rather scarce. This research aimed to determine the composition of volatile dan non-volatile compounds of the rhizome. The volatile compound was analyzed using solid phase microextraction gas chromatography mass spectrometry (SPME GC-MS), while non-volatile compound was determined by Ultra-high performance liquid chromatography-high resolution mass spectrometry (UHPLC-HRMS). The experiment by SPME GC-MS successfully identified 31 compounds with monoterpenes showing the most abundant group at 54 %. The main volatile compounds are β-Phellandrene, β-pinene, γ-Terpinene and α-pinene, then followed by sesquiterpene and terpene, namely humulene and terpinen-4-ol, respectively. Furthermore, analysis using UHPLC-HRMS detected 37 compounds with some pre dominant compounds, i.e. zerumbone, choline, isoleucine, phenylalanine, afzelin and malic acid. These findings indicate that black bangle rhizome is rich in various volatile and non-volatile compounds, especially terpenoid, flavonoid, amino acid and malic acid, some of which have certain bioactivities.